Lamellar versus Micellar Structures—Aggregation Behavior of a Three‐Chain Cationic Lipid Designed for Nonviral Polynucleotide Transfer. Issue 10 (8th May 2015) - Wölk, Christian; Janich, Christopher; Pawlowska, Dorota; Drescher, Simon; Meister, Annette; Hause, Gerd; Dobner, Bodo; Langner, Andreas; Brezesinski, Gerald
Abstract The aggregation behavior of a cationic lipid, N‐[6‐amino‐1‐oxo‐1‐(N‐tetradecylamino)hexan‐(2S)‐2‐yl]‐N′‐{2‐[N, N‐bis(2‐aminoethyl)amino]ethyl}‐2, 2‐ditetradecylpropandiamide (DiTT4), is investigated in aqueous dispersions at different pH values (5, 7.3, and 10). An unusual aggregation behavior is observed whereby DiTT4 forms bilayer structures at pH 10 and 7.3. At pH 5, rod‐like micelles are the dominant aggregate form. The thermotropic and lyotropic behavior is studied using differential scanning calorimetry, small‐angle X‐ray scattering, and FTIR spectroscopy. In addition, investigations at the air–water interface are performed by recording area–pressure‐isotherms and infrared reflection–absorption (IRRA) spectra. Complementary dynamic light scattering experiments and transmission electron microscopy (TEM and cryoTEM) are also used. The ability of DiTT4 to complex plasmid DNA is investigated using fluorescence techniques and zeta potential measurements. Cell culture experiments demonstrate the ability of DiTT4 to enhance plasmid transfer in A549 cells.